Place and Being: Higher Education as a Site for Creating Biskabii---Geographies of Indigenous Academic Identity - McAlpin, Jennifer Dawn (2015)
240 p. Thesis (Ph.D.)--University of Illinois at Urbana-Champaign, 2008. I use an Indigenous decolonizing process, as seen through a Dine and/or Anishinaabe lens. The approach can be understood in Dine and Anishinaabe terms as Hozho nahazdlii', Andaa Wenjigewin and Mino-Bimaadiziwin, respectively. These paradigms are related to auto-ethnographic and heuristic approaches to knowledge that center on the lived experiences of the researcher as the primary interpretive framework for analysis. U of I Only Restricted to the U of I community idenfinitely during batch ingest of legacy ETDs